A new acuariid species (Spirurida, Acuariidae) and other nematodes from Hydromys (Muridae, Hydromyinae) from Papua, Indonesia and Papua New Guinea - Smales, Lesley R. (Zootaxa, 2006)
From a survey of the intestinal helminths of 8 common water rats, Hydromys chrysogaster, and 1 Shaw Mayer’s water rat, Hydromys shawmayeri, from Papua New Guinea and 1 H. chrysogaster from Papua Indonesia, an acanthocephalan, Porrorchis hydromuris, a cestode Hymenolepis diminuta, a notocotylid and a psilostomid trematode and the nematodes Heterakis fieldingi, Subulura sp., Toxocara mackerrasae, Trichuris sp., Uncinaria hydromyos were found, all being new records for Hydromys in the Island of New Guinea. Tikusnema intersedis sp. nov. (Acuariidae), differing from its congenors in the number of teeth on the leaves of the pseudolabia and the length and morphology of the left spicule, was described from H. chrysogaster. Similar life styles and diets provide a common link between the rodents hosts of Tikusnema spp. The commonalities between the helminth communities of H. chrysogaster in northern Australia and New Guinea support the hypothesis that H. chrysogaster originated in New Guinea and subsequently migrated south.